Hubungan Lama Pemberian ASI Dengan Tingkat Keparahan Karies Pada Anak Usia 1-2 Tahun Di Posyandu Wilayah Kerja Puskesmas Andalas Kota Padang - Dilla Azana Fitri; Bambang Ristiono; Hidayati Hidayati (Andalas Dental Journal, 2021)
Background: Early Childhood Caries (ECC) is suspected of tooth decay that occurs in deciduous teeth. ECC is a significant problem in developing countries, which is exacerbated by low social status and malnutrition. Factors that can affect caries transfer in deciduous teeth are milk consumption at night and prolonged breastfeeding. Objective: This study aimed to support the long association of breastfeeding with severity of caries in children aged 1-2 years in the work area of Andalas Health Center, Padang City. Method: This study was an observational study with a cross sectional design. The number of research respondents is 45 children aged 1-2 years who are at the Posyandu in the Andalas Community Health Center working area. All tooth surfaces were evaluated and the scores of each tooth were calculated using a caries severity index. The average score in this study was 1.22 and grouped into three categories. A score of 0 for non-caries, a score of 0 <n <1.22 for mild caries and a score of ≥ 1.22 for severe caries. Analysis of data on the long association of breastfeeding with caries severity was carried out by chi square test. Results: The results of this study prove that the relationship was questioned (p <0.05) on the duration of breastfeeding with the severity of caries in children aged 1-2 years. Conclusion: Breastfeeding has many benefits for children, but provides breast milk for a long time and in the wrong way such as giving breast milk at night until children sleeps without cleaning can increase the risk of caries in children.